PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP MINAT KUNJUNGAN ULANG PASIEN RAWAT JALAN DENGAN KEPUASAN SEBAGAI VARIBEL INTERVENING DI RS AMELIA PARE - Rachmadana, Divya; Soelistya, Djoko; Suyoto, Suyoto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
This study aims to examine the factors influencing the interest in revisiting outpatients at Amelia Pare Hospital. Specifically, it analyzes the impact of service quality, facilities, and satisfaction on the interest in repeat visits, with satisfaction as an intervening variable. The research uses a quantitative approach, with a population of patients who revisited the hospital and a sample of 180 respondents. Data analysis was conducted using Smart-PLS 4.0. The findings indicate that service quality (X1) has a direct effect on the interest in revisiting outpatient services (Y), while facilities (X2) also directly influence the interest in repeat visits (Y). Additionally, service quality (X1) directly affects patient satisfaction (Z), and satisfaction (Z) has a direct impact on the interest in repeat visits (Y). Moreover, service quality (X1) indirectly influences the interest in repeat visits through satisfaction (Z), indicating partial mediation, and facilities (X2) also indirectly influence repeat visit interest through satisfaction (Z). Based on these results, it is recommended that Amelia Pare Hospital enhance its service quality to improve patient satisfaction and increase the likelihood of repeat visits.